2018
DOI: 10.1007/s40618-018-0922-0
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation alterations as therapeutic prospects in thyroid cancer

Abstract: Based on what was discussed in this review, we suggest that integration of epigenetic and targeted therapies into conventional treatments will reduce the occurrence of refractory radioiodine differentiated thyroid cancer and improve the outcomes in aggressive thyroid cancer patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 59 publications
0
13
0
Order By: Relevance
“…The aberrant DNA methylation of promoters and enhancers affects gene expression. Hypermethylation can lead to the silencing of tumor suppressor genes, leading to carcinogenesis; common examples in thyroid cancer include Ras association domain family 1; isoform A ( RASSF1A ); cyclin-dependent kinase inhibitor 2A ( CDKN2A or P16INK4A ); death-associated protein kinase1 ( DAPK ); tissue inhibitor of metalloproteinase-3 ( TIMP3 ); SLC5A8 ; SLC5A5 ; thyroid stimulating hormone receptor ( TSHR ); PTEN ; retinoic acid receptor β2 ( RARβ2 ); RAP1 GTPase activating protein (RAP1GAP); and fibroblast growth factor receptor (FGFR) 2 [ 73 , 74 , 75 , 76 ]. Targeted methylation analysis showed that PTC is more likely to exhibit hypomethylation than hypermethylation, compared with a normal thyroid; this is contrasted to FTC, which displays more hypermethylations than hypomethylations [ 76 , 77 ].…”
Section: Molecular Landscape Of Follicular Cell-derived Thyroid Cancermentioning
confidence: 99%
“…The aberrant DNA methylation of promoters and enhancers affects gene expression. Hypermethylation can lead to the silencing of tumor suppressor genes, leading to carcinogenesis; common examples in thyroid cancer include Ras association domain family 1; isoform A ( RASSF1A ); cyclin-dependent kinase inhibitor 2A ( CDKN2A or P16INK4A ); death-associated protein kinase1 ( DAPK ); tissue inhibitor of metalloproteinase-3 ( TIMP3 ); SLC5A8 ; SLC5A5 ; thyroid stimulating hormone receptor ( TSHR ); PTEN ; retinoic acid receptor β2 ( RARβ2 ); RAP1 GTPase activating protein (RAP1GAP); and fibroblast growth factor receptor (FGFR) 2 [ 73 , 74 , 75 , 76 ]. Targeted methylation analysis showed that PTC is more likely to exhibit hypomethylation than hypermethylation, compared with a normal thyroid; this is contrasted to FTC, which displays more hypermethylations than hypomethylations [ 76 , 77 ].…”
Section: Molecular Landscape Of Follicular Cell-derived Thyroid Cancermentioning
confidence: 99%
“…Frequent epigenetic silencing of the RASSF1A in thyroid carcinoma has been highlithed (109) alone or with NORE1A methylation and BRAF V600E mutations (110). RASSF1 methylation can be used as the therapeutic determinant in thyroid malignancies (111). In a meta-analysis it was reported as the most significant hyper-methylated region within thyroid carcinomas (112).…”
Section: Discussionmentioning
confidence: 99%
“…The hypermethylation of DAPK leads to inactivation of the MAPK signalling pathway. Due to the important roles of PTEN and DAPK in early TC diagnosis, cancer screening, and treatment prospects, they are assigned the methylation status of a biomarker [ 68 , 103 ]. Different signaling pathways and BRAF inhibitors in thyroid cancer.…”
Section: Different Signalling Pathways and Braf Inhibitors In Tcmentioning
confidence: 99%